Analysis of Mobile Banking Adoption with a Modified Technology Acceptance Model (TAM) on the Mybca Mobile Banking Application - Widjaja, Adeline Louisa; Noviaristanti, Siska (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Digital transformation is reshaping all industries, including the banking sector. One key driver is the shift in customer behavior toward smartphone-based financial transactions. Bank BCA introduced the myBCA mobile banking application to address this trend; however, its adoption remains relatively low. This study investigates the factors influencing customer adoption of myBCA, addressing a research gap in understanding mobile banking adoption in the context of a new platform with low user uptake. The study extends the Technology Acceptance Model (TAM) by integrating six additional variables: Perceived Trust (PT), Social Influence (SI), Perceived Risk (PR), Perceived Security (PS), and Habit (HT), alongside Perceived Usefulness (PU) and Perceived Ease of Use (PEU). Intention to Use (ITU) is positioned as a mediating variable. Data were collected from 400 respondents via online surveys using simple random sampling. Analysis was conducted using PLS-SEM with SmartPLS. Results indicate that PU, PEU, PT, SI, PS, and HT positively influence Adoption of Mobile Banking (AMB) through ITU, while PR has a negative effect. ITU explains 59.5% of the variance, while AMB is explained by 48.1%. The novelty of this research lies in its comprehensive model that incorporates behavioral, security, and trust-related variables to explain adoption in a newly launched mobile banking platform—an area not widely examined in existing TAM-based studies. This study offers theoretical contributions for future research and practical insights for Bank BCA to enhance myBCA adoption by focusing on trust-building, security assurance, and habitual engagement strategies.